2014
DOI: 10.7314/apjcp.2014.15.13.5187
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Fingernail Selenium and Thyroid Cancer Risk: A Case-Control Study in French Polynesia

Abstract: Background: Numerous studies have suggested that selenium deficiency may be associated with an increased risk for several types of cancer, but few have focused on thyroid cancer. Materials and Methods: We examined the association between post-diagnostic fingernail selenium levels and differentiated thyroid cancer risk in a French Polynesian matched case-control study. Conditional logistic regression models were used to estimate odds ratios and 95% confidence intervals. Results: The median selenium concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In vitro study showed that Se is able to decrease thyroid cancer growth [ 11 ]. In one study Se was inversely correlated with stages of thyroid cancer [ 12 ], but in a post-diagnosis study there was no association between fingernail selenium levels and thyroid cancer risk [ 13 ].…”
mentioning
confidence: 99%
“…In vitro study showed that Se is able to decrease thyroid cancer growth [ 11 ]. In one study Se was inversely correlated with stages of thyroid cancer [ 12 ], but in a post-diagnosis study there was no association between fingernail selenium levels and thyroid cancer risk [ 13 ].…”
mentioning
confidence: 99%
“…This result is not consistent with previous studies that have investigated the link between low Se levels and thyroid cancer. In this regard, we speculate that the irrelevance of this study may stem from the method of Se measurement, which is available in whole blood, serum (79,80), urine (81), nails (82), and questionnaires (83). The Se levels of the subjects in this study were inferred from the diet, so it has an information bias.…”
Section: Se and Thyroid Tumorsmentioning
confidence: 90%
“…In contrast, other studies do not provide evidence of a significant association between Se deficiency and thyroid cancer [105,106]. Table 2 presents some studies and results conducted on Se and/or selenoproteins in serum, tissue, fingernail and urine of thyroid cancer subjects.…”
Section: Selenium and Thyroid Cancermentioning
confidence: 99%